Are Traditional Clinician Recruitment Practices, Using Non-Virtual Offline Approaches, Redundant in the Age of Web-Based Technology Platforms? - Huynh, Peter (Digital Repository of Theses, 2024)
The U.S. healthcare staffing market size is expected to reach 34.7 billion by 2030, exhibiting a growth rate 5.6% from 2022 to 2030. The increasing geriatric population is leading to a rising demand for medical services and a shortage of nurses and other medical staff. Our society and the expanding population are living longer but becoming infirm and getting sicker. Our population is experiencing higher rates of morbidity and lower rates of mortality. The cost of temporary staffing is likely to drive the market in the coming years. U.S. Bureau of Labor Statistics predicts 19% growth in travel nursing. Clinicians must be recruited to effectively care for an aging and sicker population. The demographics of such a clinical force is younger and more technologically savvy and the past generations of nursing and medical staff are now aging into retirement leading to a significant clinician shortage and an ensuing problem for the healthcare staffing arena. Furthermore, approximately five hundred thousand nurses plan to retire from the workforce over the coming years. The Association of American Medical Colleges predicts there will be a shortage of up to fifty-five thousand primary care physicians by 2032 leading to a crisis in clinical staffing. The question being posed is whether healthcare systems are better served using online platforms and dispensing of the older traditional approaches to clinician recruitment such as offline non virtual, hard copy printed resources. This research uses a combination of qualitative data collection (questionnaires) and quantitative data analysis (scaling and scoring system) to ascertain the potential best approach for clinician engagement and recruitment now and in future years. The results observed showed that clinician candidates continue to rely on both virtual and non-virtual traditional approaches as a mechanism for locating job opportunities and non-virtual platforms play an important role in the clinician‟s due diligence and decision-making process. Thus, traditional recruitment approaches are by no means a redundant resource in an age of web-based technology.